Strategi Pengembangan Objek Wisata Alam Sulilidi Desa Baebunta Luwu Utara - Rifka Taruk Salong; Jens Batara Marewa; Mince Batara (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
The purpose of this research is to determine the development strategy carried out by the government to develop the Sulili Natural Tourism Object. The type of research used in this research is descriptive qualitative research. The results of research on the SWOT matrix show that there are several alternative strategies to support the development of the Sulili natural tourist attraction. Based on the results of SWOT analysis research on the IFAS (Internal Factor Analysis Summary) matrix calculation, the score for strength/strength is 1.96 while the weakness/weakness is 1.08 if totaled, so the total score for internal factors is 3.04. The results of this analysis show that the internal condition of the Sulili natural tourist attraction is in a strong position where the Sulili natural tourist attraction has the strength to overcome weaknesses. In the EFAS matrix, the score obtained for opportunities is 1.67, while for threats it is 1.42 if totaled, so the total score obtained for external factors is 3.09. The results of this analysis show that the Sulili natural tourist attraction is in a good external position and responds strongly to opportunities and avoids threats. From the results of the SWOT diagram, the coordinate points (X,Y) are obtained, namely (0.88; 0.25), so that the intersection point is obtained in square I, which is a very favorable situation for the Sulili natural tourist attraction.